The modern method of statistical analysis (modling structural equation) - belouadah, rabia; saad, sabah (Journal of Social Sciences and Humanities, 2022)
the aims of this research are to treat the necessary elements of the analysis of the confirmatory factor. , the two researchers concentrated on the methodological side of this method as it facilitates the understanding of the necessary elements of the different rational and logical sides of the confirmatory factor analysis method .we find that the two researchers use the construction of model confirmatory factor in several stages with approaching model structural equation and this lead to the final conclusions equation and this lead to the final conclusions.